KAJIAN ELEMEN VISUAL IKLAN GO-JEK VERSI KARANGAN BUNGA - Fatimah Yasmin Hasni (Universitas Mercu Buana, 2020)
The development of the advertising world is now increasingly innovating in creativity. Advertising is a reflection of the image of a company, of course, the concept of creativity refers to the character of the company so that the delivery of messages can arrive according to the positioning of the mind of the audience. Various products and services have their strategies to strengthen their positioning. One of them is an application-based company called GO-JEK.GO-JEK in its advertisement carries the theme of floral arrangements with the slogan #AnakBangsaBisa. In commemoration of the 73rd independence day of the Republic of Indonesia, GO-JEK expressed its gratitude to the sons and daughters of the nation who had inspired and succeeded in bringing Indonesian names to the ends of the world, even into space. This was revealed through the site and billboards themed flowers.This study aimed to study the GO-JEK floral arrangement advertising design as a creative element of speech culture through floral arrangements in the advertising world. The method in this study is descriptive qualitative, which will examine the concept of visual strategy design in the advertisement applied by GO-JEK by reviewing the visual appearance related to color, the shape in the form of fields, illustrations, typography, icons/symbols, and layouts used. Output targeted in the study, the results of the research can be published in national-level journals.Based on the above, the research reviews the GO-JEK advertisement version of the visual strategy of GO-JEK, to appreciate the development of contemporary advertising content, especially developments in the advertising world.